The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2007
DOI: 10.1115/1.2748815
|View full text |Cite
|
Sign up to set email alerts
|

The Performance of the Kalina Cycle System 11(KCS-11) With Low-Temperature Heat Sources

Abstract: The possibility of exploiting low-temperature heat sources has been of great significance with ever increasing energy demand. Optimum and cost-effective design of the power cycles provide a means of utilization of low-temperature heat sources which might otherwise be discarded. In this analysis, the performance of the Kalina cycle system 11 (KCS11) is examined for low-temperature geothermal heat sources and is compared with an organic Rankine cycle. The effect of the ammonia fraction and turbine inlet pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(27 citation statements)
references
References 9 publications
2
25
0
Order By: Relevance
“…Bombarda et al [14] conducted a comparison between the thermodynamic performances of Kalina cycle and an ORC cycle, for the case of heat recovery from two diesel engines, and the calculation results show that the quantities of net electric power produced by the Kalina cycle and the ORC are about the same. Hettiarachchi et al [16] investigated the performance of the Kalina cycle system with low temperature heat sources and found that the dual pressure KC has better overall performance at moderate pressures than that of the ORC.…”
Section: Introductionmentioning
confidence: 98%
“…Bombarda et al [14] conducted a comparison between the thermodynamic performances of Kalina cycle and an ORC cycle, for the case of heat recovery from two diesel engines, and the calculation results show that the quantities of net electric power produced by the Kalina cycle and the ORC are about the same. Hettiarachchi et al [16] investigated the performance of the Kalina cycle system with low temperature heat sources and found that the dual pressure KC has better overall performance at moderate pressures than that of the ORC.…”
Section: Introductionmentioning
confidence: 98%
“…(1) (gross power density) taken at standard conditions DT ¼ 20 C and T ¼ 300 K. The average seawater density q is taken as 1025 kg m À3 , the seawater specific enthalpy c p as 4000 J kg À1 K À1 , and the OTEC combined turbo-generator efficiency e tg as 0.75. Despite their simplicity, the proposed power formulas capture the basic behavior of OTEC systems based on pure-fluid, low temperature Rankine cycles, with thermodynamic efficiencies approximately half the Carnot limit of DT over T. If more complex cycles were considered, e.g., of the Kalina type [22], Eqs. (1) and (2) should be modified accordingly.…”
Section: Otec Simulationsmentioning
confidence: 99%
“…At present, the heat recovery from high temperature gases, as in the modern combined cycles, or in multi-megawatts coal thermoelectric plants, is monopolized by the steam Rankine cycles and the more believable application of the Kalina cycle is restricted to medium-low temperatures heat sources (typical maximum temperatures of 300-400 • C in the case of heat recovery, and 100-120 • C in the binary geothermal plants) and to small power conversion systems [8,9,10,11].…”
mentioning
confidence: 99%